Efficient intramolecular singlet fission in spiro-linked heterodimers [research data] - Kefer, Oskar; Ahrens, Lukas; Han, Jie; Wollscheid, Nikolaus; Misselwitz, Erik; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.; Buckup, Tiago (Universität, 2024)
We investigate intramolecular singlet fission (iSF) of spiro-linked azaacene heterodimers by time-resolved spectroscopy and quantum chemical calculations. Combining two different azaacenes through a nonconjugated linker using condensation chemistry furnishes azaacene heterodimers. Compared to their homodimers, iSF quantum yields are improved at an extended absorption range. The driving force of iSF, the energy difference between the S1 state and the correlated triplet pair 1(TT), is tuned by the nature of the heterodimers. iSF is exothermic in all of the herein studied molecules. The overall quantum yield for triplet exciton formation reaches approximately 174%. This novel concept exploits large energy differences between singlet electronic states in combination with spatially fixed chromophores, which achieves efficient heterogeneous iSF, if the through-space interaction between the chromophores is minimal.